Critical care after lung resection: CALoR 1, a single‐centre pilot study1. (December 2015) - McCall, P. J.; Macfie, A.; Kinsella, J.; Shelley, B. G.
Summary: Lung resection is associated with significant perioperative morbidity, and a proportion of patients will require intensive care following surgery. We set out to characterise this population, assess their burden of disease and investigate the influence of anaesthetic and surgical techniques on their admission rate. Over a two‐year period, 1169 patients underwent surgery, with 30 patients (2.6%) requiring unplanned intensive care. Patients requiring support had a higher mortality (0.2% vs 26.7%, p < 0.001). Logistic regression (following adjustment for Thoracoscore) revealed that an open surgical approach was associated with higher likelihood of admission (p = 0.025, odds ratio = 5.25). There was also a trend towards increased likelihood of admission in patients who received volatile anaesthesia (p = 0.061, odds ratio = 2.08). This topic has been selected for further investigation as part of the 2015 Association of Cardiothoracic Anaesthetists (ACTA) second national collaborative audit, with this study providing pilot data before a multi‐centre study.